Kualitas Otak-otak Ikan Bandeng (Chanos-chanos) Dengan Kombinasi Tepung Pisang Kepok (Musa paradisiaca L.) Dan Tepung Buah Mangrove (Rhizopora mucronata) - Lemba, Satryani; Mile, Lukman; Nento, Wila Rumina (Jambura Fish Processing Journal, 2025)
Milkfish can be utilized in making otak-otak by replacing tapioca flour with kepok banana flour and mangrove flour, through food diversification as an effective solution. This study aims to determine the organoleptic value, chemical characteristics and fiber content of the formulation of milkfish, kepok banana flour (Musa Paradisiaca L.) and mangrove fruit flour (R. mucronata). The research method was carried out through several stages, including making kepok banana flour, making mangrove fruit flour and making milkfish brain-brain. Data analysis used a completely randomized design (CRD) with 3 treatments and 2 replicates. The data obtained will be analyzed with One Way ANOVA. If each treatment is significantly different then Duncan's further test. The results showed that the organoleptic value of milkfish brain-boxes influenced the level of panelists' liking, namely appearance, taste, texture, but had no effect on aroma. Fish brain-brain products have chemical content, namely: water content (20.96% - 58.34%), protein content (5.41% - 6.36%), fat content (3.42% - 5.93%), ash content (1.32% - 1.65%), carbohydrate content (24.74% - 53.12%) and fiber content (6.76% - 21.87%).